(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The quality of the lithosphere, biosphere, atmosphere, hydrosphere, and biosphere are all impacted by environmental contamination. Over the past 20 years, a lot of work has been done to mitigate pollution sources and clean up contaminated water and land. In both academic and practical circles, phytoremediation is becoming more and more popular since it is less expensive and has fewer negative consequences than chemical and physical techniques